Meningkatkan Hasil Belajar PKn Melalui Model Pembelajaran CIRC - Pasaribu, Elliwati (JURNAL GLOBAL EDUKASI, 2020)
Abstract: This research is based on the lack of teachers' understanding of techniques and how to integrate national character development in teaching and learning activities, especially at SDN 016529 BP. Mandoge. The objectives of this Classroom Action Research are: (1) Improving Student Achievement in Basic Material State Formulation Process through CIRC Learning Method Class VI Class VI PKn SDN 016529 BP. Mandoge discrit Bandar Pasir Mandoge academic year 2016/2017; (2) The classroom action research was carried out in class VI, totaling 20 students. The subjects of this study were PKN teachers and grade VI students of SDN 016529 BP. Mandoge, data were collected through observation, interviews, tests, and study documentation. This classroom action research was conducted in 2 cycles, consisting of planning, acting, observing and reflecting. The learning outcomes in the first cycle reached an average value of 69.77% after the first cycle and the second cycle, the reflection and recommended values reached an average value of 85.53%. Keywords: basic state formulation process; CIRC Abstrak: Penelitian ini dilator belakangi masih kurangnya pemahaman guru tentang teknik dan cara mengintegrasikan pembangunan karakter bangsa dalam kegiatan belajar mengajar, khususnya di SDN 016529 BP. Mandoge. Adapun tujuan dari Penelitian Tindakan Kelas ini adalah: (1) Meningkatkan Prestasi Belajar Siswa Materi Pokok Proses Perumusan Dasar Negara Melalui Metode Pembelajaran CIRC Pelajaran PKN Kelas VI SDN 016529 BP. Mandoge Kec. Bandar Pasir Mandoge TP. 2016/2017; (2) Penelitian tindakan kelas dilaksanakan dikelas VI yang berjumlah 20 orang siswa. Subjek penelitian ini adalah guru PKN dan siswa kelas VI SDN 016529 BP. Mandoge, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Hasil belajar pada siklus I mencapai nilai rata-rata 69,77% setelah siklus I dan siklus II, refleksi dan rekomendasi nilai rata-rata mencapai 85,53%. Kata Kunci: CIRC; proses perumusan dasar negara